2000
DOI: 10.1136/jamia.2000.0070196
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Computer and Manual Reminders on Compliance with a Mental Health Clinical Practice Guideline

Abstract: In an outpatient mental health clinic, computer reminders were shown to be superior to manual reminders in improving adherence to a clinical practice guideline for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 16 publications
0
73
0
7
Order By: Relevance
“…24 That finding was consistent with another report that electronic feedback increases the rate at which PCPs document depression in their clinical notes compared to PCPs who are not electronically informed of the diagnosis. 23 However, even valid and pertinent EMR reminders for appropriate depression care must compete for physician attention with overt patient concerns (e.g., fatigue, insomnia, and back pain) plus the routine primary care tasks (e.g., cancer screening and managing cardiovascular disease) to be performed within the limitations of the typical 15-minute primary care encounter. Addressing these presenting complaints and somatic symptoms can distract busy PCPs from counseling their patients for depression or from delivering appropriate care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 That finding was consistent with another report that electronic feedback increases the rate at which PCPs document depression in their clinical notes compared to PCPs who are not electronically informed of the diagnosis. 23 However, even valid and pertinent EMR reminders for appropriate depression care must compete for physician attention with overt patient concerns (e.g., fatigue, insomnia, and back pain) plus the routine primary care tasks (e.g., cancer screening and managing cardiovascular disease) to be performed within the limitations of the typical 15-minute primary care encounter. Addressing these presenting complaints and somatic symptoms can distract busy PCPs from counseling their patients for depression or from delivering appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…14±20 However, few studies have reported clinical outcomes when an EMR system is used to treat a chronic medical problem, 21,22 or a psychiatric disorder. 23 The EMR's technical features and effectiveness in altering provider behavior through timely reminders make it an attractive modality for improving the quality of care and subsequent clinical outcomes for major depression in primary care practice. Previously, we reported that PCPs respond quickly when electronically informed of their patients' depression diagnosis (median response time: 1 day), and that when PCPs electronically indicated their agreement with the diagnosis, they were more likely to make a notation of depression in their patients' medical record and to initiate treatment for the depressive episodes at 1 month than were PCPs who disagreed with the diagnosis.…”
mentioning
confidence: 99%
“…This is important since as many as half of depressed patients in VA PC use non-VA care for some aspect of their overall healthcare. 37 Although treatment rates we observed in this study are relatively high, other VA studies have noted that duration of antidepressant use and adequacy of follow-up are elements of guideline-adherent depression treatment that may have more room for improvement in VA. [18][19][20] Since other studies of decision support interventions for depression care have also generally shown improvement in screening but less impact on treatment, [38][39][40] added systems changes such as care manager support may be necessary to improve depression treatment processes and outcomes. 35 Finally, as an implementation study with local tailoring, only one site successfully implemented the reminders in both neurology and PC clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that effective HIT use is associated with improved preventive care (Larsen et al 1989;Litzelman et al 1993;Willson et al 1995;Overhage et al 1996;Cannon & Allen 2000, Demakis et al 2000Teich et al 2000, Dexter et al 2004, reduced complications (Larsen et al 1989;Kucher et al 2005), fewer adverse events (Evans et al 1992), medical errors (Bates et al 1998;Evans et al 1998), decreased resource utilization (Tierney et al 1993;Bates et al 1999), and lower health care costs (Tierney et al 1993). However, HIT must be implemented carefully and thoughtfully to produce these benefits.…”
Section: Introductionmentioning
confidence: 99%